1148 Working environment and work retention of ageing workers. (24th April 2018) - Schaumburg, I; Melchior Poulsen, O; Andersen, LL
Abstract : Introduction: Demographic changes will profoundly decrease the fraction of the population being at working age in the Nordic countries. This will increase pressure on the Nordic welfare systems, and increased work participation and prolonged work life is therefore high on the political agenda. A recent project showed that the working environment has high impact on early retirement to both disability pension and voluntary pension. However, the project also revealed that knowledge is still lacking on working environment predictors of early retirement particularly in occupations with high risk of early retirement (e.g. blue collar workers with strenuous work). Methods: Data from the Danish 'Work Environment and Health' survey, which is performed every second year among a representative sample of wage earners between 18 and 64 years (50 806 persons in 2012; 50 875 persons in 2014; and 65 741 persons in 2016), will be analysed for cross-sectional and prospective associations between working environment and intention to retire early. Analyses will be adjusted for various confounders and stratified for socioeconomic position and selected larger job groups. Results: The Nordic project found the following working environment factors to be predictors of early retirement: Occupational accidents, whole-body vibration, physical work demands (strenuous work, heavy lifting, prolonged standing), quantitative work demands (work speed and time pressure), job control, influence at work, leadership support, conflicts at work, bullying/harassment, and job satisfaction. Results from analysis in 'Work Environment and Health' of the differential impact of the different working environment factors on intention to retire early in different occupations will be presented. Conclusion: The working environment factors of major importance for early retirement in occupations with high risk of early retirement are identified, and possible working environment interventions to improve work retention and prolong work-life are discussed.